Polki w Norwegii – decyzje i plany prokreacyjne - Łobodzińska, Anna (Studia Demograficzne, 2016)
Given the scale and pace of post-EU accession migrations from Poland, as well as age and gender structure of their participants, an increased interest in family behaviour and intentions of this group has been recently noted. The observed interrelations between migration and family building processes are multidimensional. Thus, this study aims to investigate interrelations between migration, childbearing decisions and intentions of Polish female migrants in Norway. The paper is based on a survey research conducted among Polish female migrants in 2014–2015. The results show that majority of immigrants was childless upon arrival. For those, who had a child before migration, the mobility occurred in a relatively early stage of family formation process. However, a concentration of births shortly after migration can be observed. This concerns mostly women migrating to join their husbands or partners. An opposite evidence is observed regarding respondents who had one child upon arrival to Norway – only few of them proceeded to the second birth. Almost 58% of respondents wants to give birth to their next child in Norway. More importantly, majority of women planning a long-term stay in Norway still has positive or uncertain childbearing intentions.